Hydrothermal Synthesis of NiCo2O4/Activated Carbon Composites for Supercapacitor with Enhanced Cycle Performance. Issue 18 (28th June 2017) - Xu, Jingcai; Liu, Fei; Peng, Xiaoling; Li, Jing; Yang, Yanting; Jin, Dingfeng; Jin, Hongxiao; Wang, Xinqing; Hong, Bo
Abstract: Owing to the advantages of the good conductive AC and high capacitive NiCo2 O4, We prepared a series of NiCo2 O4 /AC composites by a hydrothermal method. The morphology of NiCo2 O4 /AC composites indicate the NiCo2 O4 nanoplates with diameters of about 0.5∼1 μm and thickness of about 20 nm are coated on AC. The electrochemical investigation demonstrate that the specific capacitances of NCO‐AC‐3 (containing 47 % NiCo2 O4 ) are 273.5 F g −1 and the capacity retention still retains at 96 % (262.6 F g −1 ) after 3000 cycles at current density of 1 A g −1, especially, the cycling stability maintain more stable at high current density. Therefore, the low‐cost NiCo2 O4 /AC composites can serve as a promising electrode material for high performance supercapacitors due to the synergistic effect between the electric double‐layer capacitance of porous AC and the pseudocapacitance of NiCo2 O4 nanoplates. Abstract : NiCo2 O4 nanoplates with diameters of about 0.5∼1 μm and thickness of about 20 nm coated on AC are successfully prepared by a hydrothermal method. The specific capacitances of NiCo2 O4 /AC composites is 273.5 F g −1 and the capacity retention still retains at 96 % after 3000 cycles at current density of 1 A g −1, especially, the cycling stability maintain more stable at high current density. Therefore, the low‐cost NiCo2 O4 /AC composites can serve as a promising electrode material for high performance supercapacitors.